Ekosystemtjänster i gräsmarker - Pettersson, Anna (2020)
The interest in the importance of grasslands in Europe has been addressed by the EU project SUPER-G, whose objective is to increase the productivity of grasslands while also exploring how these lands contribute to other types of ecosystem services, i.e. various benefits that humans receives from nature. As part of the project, I have in this essay chosen to do a literature study where I focus on the ecosystem services biodiversity, recreation, food production and carbon sequestration, and explore the importance of cultivated grasslands (permanent grasslands) and non-cultivated grasslands (semi-natural pastures) for these services. I also briefly describe three different kinds of grasslands and what the definition of ecosystem services is. In a survey conducted by SUPER-G 22 farmers in Sweden were asked about their grasslands and their importance for various ecosystem services. I have also compiled this data and drawn conclusions from this. The results of the literature study show that semi-natural pastures make a great contribution to biodiversity by housing a large number of plant species. Semi-natural pastures are also important for people's recreation as an open landscape is closely linked to quality of life. On the other hand, permanent grasslands make a greater contribution to food production as animal feed. The survey results show that farmers find that their natural pastures contribute most to biodiversity, pollination, recreation and tourism as well as good quality of water, while permanent grasslands are considered to contribute most to carbon reduction and reduced greenhouse gas emissions and less flooding and erosion inhibition. My conclusions are that the survey and the literature study coincide with regard to semi-natural pastures and biodiversity ecosystem services and recreation. They also show similar answers when it comes to permanent grasslands and grazing animals that can be considered to be closely related to food production. Regarding carbon storage, farmers believe that permanent grasslands contribute more to this ecosystem service than semi-natural pasture lands do, but the literature study shows some uncertainties in the matter. Since the threats against Europe's grasslands are many, hopefully future studies can provide more clarity on the importance of grasslands to humans and how we should best manage them. After writing this paper there is no doubt that they are well worth preserving.